4,6-Disubstituted pyrimidine-based microtubule affinity-regulating kinase 4 (MARK4) inhibitors: synthesis, characterization, in-vitro activity and in-silico studies - Haque, Ashanul; Alenezi, Khalaf M.; Rasheed, Mohd. Saeed Maulana Abdul; Rahman, Md. Ataur; Anwar, Saleha; Ahamad, Shahzaib; Gupta, Dinesh (Frontiers in Pharmacology, 2025)
IntroductionAlzheimer’s disease (AD) is a neurodegenerative disorder that significantly impacts the cognitive function and memory of a person. Despite the significant research efforts, the ability to completely prevent or effectively treat AD and its related dementias remains limited. Protein kinases are integral to AD pathology and represent promising targets for therapeutic intervention.MethodsA series of pyrimidine-based compounds 4-(4-(arylsulfonyl)piperazin-1-yl)-6-(thiophen-3-yl)pyrimidine derivatives (8-14) were synthesized and characterised. ATPase inhibition was carried out against the MARK4 enzyme. Molecular docking and molecular dynamics (MD) simulation at 500 ns was carried out against MARK4 (PDB: 5ES1). The drug-likeness feature and toxicity of the molecules were evaluated using QikProp and other tools.ResultsCompounds were synthesized following a multi-step approach and characterized using multi-nuclear magnetic resonance (1H/13C-NMR) and mass spectrometry. ATPase inhibition assay of the compounds against MARK4 showed an IC50 value in the micromolar (μM) range. The results of the docking studies were consistent with the in-vitro experiments and identified (9) and (14) as the candidates with the highest affinity towards MARK4. MD simulation further supported these results, showing that the binding of ligands stabilises the target protein.ConclusionUsing experimental and theoretical approaches, we demonstrated that the reported class of pyrimidine derivatives are an excellent starting point for developing the next-generation anti-AD drugs.